2007
DOI: 10.1176/ps.2007.58.11.1489
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With a Six-Month Return to Emergency Services Among Child and Adolescent Psychiatric Patients

Abstract: These results suggest that the emergency department is being used as part of the continuum of care for patients already in treatment, particularly those displaying disruptive behavior. Additional research is needed to determine whether this recidivism is clinically indicated or reflects a lack of available or appropriate care in community settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
3
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 4 publications
4
58
3
3
Order By: Relevance
“…Although previous research showed that current involvement in and access to MH services predicted repeat ED use 14,16,33,34 , our study demonstrated that patients connected with previous resources were more likely to repeat earlier and more frequently to the PED when controlling for other variables. Past research on pediatric and adult samples shows that lack of availability from primary care during weekend and evening hours and those dissatisfied with primary care were more likely to visit the ED.…”
Section: Service Use Determinantscontrasting
confidence: 97%
See 4 more Smart Citations
“…Although previous research showed that current involvement in and access to MH services predicted repeat ED use 14,16,33,34 , our study demonstrated that patients connected with previous resources were more likely to repeat earlier and more frequently to the PED when controlling for other variables. Past research on pediatric and adult samples shows that lack of availability from primary care during weekend and evening hours and those dissatisfied with primary care were more likely to visit the ED.…”
Section: Service Use Determinantscontrasting
confidence: 97%
“…Past research on pediatric and adult samples shows that lack of availability from primary care during weekend and evening hours and those dissatisfied with primary care were more likely to visit the ED. 32,35 Also consistent with previous research 16,20 , our results indicated that patients were more likely to return to the PED if they had a history of previous psychiatric hospitalization. Previous psychiatric hospitalization also predicted earlier repeat presentations.…”
Section: Service Use Determinantssupporting
confidence: 91%
See 3 more Smart Citations